2017
DOI: 10.1021/acs.joc.7b00299
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Enolate Arylation with 3-Bromoindoles Allows the Formation of β-Carbolines

Abstract: Synthesis of substituted β-carbolines was accomplished by utilizing the catalytic enolate arylation reaction of ketones in conjunction with several 3-bromoindole derivatives. Quenching of the arylation reaction in situ with an electrophile allowed ready incorporation of functionality at the carboline C-4 position in an efficient one-pot protocol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…For instance, preparation of the natural product-relevant β-carboline ring-system was possible (→ 57 , Scheme 13). 108 This was achieved in a one-pot protocol by coupling ketones with the 3-bromoindoles 58 . When methyl ketones were used in this protocol, the resulting intermediary α-methylenyl enolate could be reacted with alkyl halide electrophiles, in a procedure analogous to that shown in Scheme 12, to functionalise the β-carboline 4-position (not shown).…”
Section: Annulation Of Unsaturated Nitrogen-containing Ringsmentioning
confidence: 99%
“…For instance, preparation of the natural product-relevant β-carboline ring-system was possible (→ 57 , Scheme 13). 108 This was achieved in a one-pot protocol by coupling ketones with the 3-bromoindoles 58 . When methyl ketones were used in this protocol, the resulting intermediary α-methylenyl enolate could be reacted with alkyl halide electrophiles, in a procedure analogous to that shown in Scheme 12, to functionalise the β-carboline 4-position (not shown).…”
Section: Annulation Of Unsaturated Nitrogen-containing Ringsmentioning
confidence: 99%
“…In most cases, the resulting modified β-carbolines were arylated exclusively at either C1 or C3; in only a few cases were 1,3-diphenyl-β-carbolines successfully synthesized (Scheme ). The structure–activity relationship analyses revealed that 1-aryl-substitution on a β-carboline bearing a carbohydrazide moiety at C3 enhanced the antitumor activity . Heteroaryl substitution (1,2,3-triazolo or pyridine moieties) on the C1 position of the β-carboline nucleus exerts a significant DNA-binding ability to the scaffold .…”
Section: Introductionmentioning
confidence: 99%
“…Driven by our interest in searching for novel small molecules for cancer therapy (Ke et al., 2019), we would like to develop an approach for quick access to these scaffolds by direct and selective connecting carbonyl motifs and C2-substituted indoles, considering that carbonyl moieties are among the most synthetic useful functional groups in organic synthesis. Previous approaches in connecting carbonyl compounds and C3 position of C2-substituted indole mainly rely on carbine insertion (Keller et al., 1977, Gibe and Kerr, 2002), nucleophilic addition (Tang et al., 2012, Vander Wal et al., 2013, Maksymenko et al., 2017), and Buchwald-Hartwig coupling reactions (Esteves et al., 2017). In all these methods, either carbonyl regents (e.g., diazo, α-bromocarbonyl, enonium species) or C3-bromoindole requires additional steps for preparation from corresponding carbonyl compounds or indoles.…”
Section: Introductionmentioning
confidence: 99%